UJI EFEK ANALGETIK EKSTRAK RUMPUT TEKI (CYPERUS ROTUNDUS L.) PADA TIKUS PUTIH JANTAN GALUR WISTAR (RATTUS NOVERGICUS) - Pandey, Putri Virgie; Bodhi, Widdhi; Yudistira, Adithya (PHARMACON, 2013)
Pain is defined as a sensory and emotional experience that is not associated with tissue damage. Nut grass (Cyperus rotundus L.) is traditionally used as a pain reliever. The objectives of this research were to find out analgesic effect of nut grass extract with concentration 3,15 g/KgBB, 6,3 g/KgBB and 12,6 g/KgBB on white male wistar. The subject in this research were 15 white male wistar which divided into 5 groups, each group consist of 3 white male wistar. Negative control group were administered with aquadest, positive control group were administered with paracetamol, and experiment groups were administered with nut grass extract. Analgesic test were examined by giving pain stimulation to treated animals, such as 65Â°C heat stimulation. The response which observed were rats licking feet or jumping response. The observation was conducted for 1 minute.Observations were conducted before extract administration, then at 30, 60, 90 and 120 minutes after administered. The results shows thatnut grass extract with concentration 3,15 g/KgBB, 6,3 g/KgBB and 12,6 g/KgBB possess analgesic effect on white male wistar, especially concentration 6,3 g/KgBB. Keywords: analgesic, nut grass extract, pain